Chileans, climate change and the natural environment: An audience segmentation study - Sapiains Arrué, Rodolfo Jorge Patricio; Azócar de la Cruz, Gabriela Alejandra; Ugarte Caviedes, Ana María; Romero Hernández, Javier Alberto (Convergencia Revista de Ciencias Sociales, 2021)
Not much research has been carried out in Latin America on the human dimensions of climate change. An audience segmentation study was conducted in Chile to explore different perspectives about this issue, using data from a national survey (n=2170). Results showed most Chileans express high levels of concern and agree climate change is happening and caused mainly by human actions. On the contrary, differences were found on worldviews, behaviors, perceptions of control among other factors, allowing the identification of three groups: Pragmatics, Neoliberals and Environmentalists. These results can contribute to the design of more effective communication strategies to increase awareness and climate action.